PENEMPATAN PEGAWAI NEGERI SIPIL (PNS) DALAM JABATAN STRUKTURAL PADA UPTD DINAS PERKEBUNAN PROVINSI KALIMANTAN TIMUR - Taufiq Kurrahman (Jurnal Paradigma (JP), 2017)
The aim of this study is to describe and analyze the placement of Civil Servants (PNS) in a structural position in UPTD Plantation Office of East Kalimantan Province. The focus of research is the implementation of education and training which consists of suitability educational background to the field of employment, an employee with suitability workload capacity, suitability of the skills and expertise of employees in the field of employment, employee competence conformity with the available pool, fitness rank / group to the position. Sources of primary data derived from interviews with selected informants, and from direct observation in the study site. While secondary data derived from the information or data held by agencies. Analysis of the data used is interactive model developed by Miles, Huberman and Saldana through condensation stages, data presentation and conclusions and verification.